Gallego Cuiñas, Ana, Otros. Ricardo Piglia y la literatura mundial, Madrid / Frankfurt, Iberoamericana / Vervuert, 2019, 210 pp. - Locane, Jorge J. (2020)
Fil: Locane, Jorge J. Universidad de Oslo; Noruega